1972
DOI: 10.1111/j.1752-1688.1972.tb05135.x
|View full text |Cite
|
Sign up to set email alerts
|

Planners as a Public in Water Resources Public Participation Programs1

Abstract: This paper suggests a number of benefits in identifying urban and regional planners as a public in public participation programs of water resources planning studies. A perspective on public participation is presented. Recent trends and developing concepts are identified: emphasis on the need to coordinate urban and regional planning activities with water resources planning, increasing system complexity, the goals and objectives orientation of planning, planning for multi‐objectives, the evaluation of a broader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1980
1980

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Sufficient public education and information transfer as an important criterion of effectiveness (Frauenglass, 1971;Tucker, 1972;Allee, 1974;Ertel, 1977) was measured in the survey by polling the individuals as to their opinions of the importance of numerous specific related tasks, including the preparation and presentation of educational materials and contact with the media. Results clearly revealed that emphasis in a training course should be placed on tasks of this type, including use of layman's language, effective graphics, and good media coverage.…”
Section: Public Education and Information Transfermentioning
confidence: 99%
“…Sufficient public education and information transfer as an important criterion of effectiveness (Frauenglass, 1971;Tucker, 1972;Allee, 1974;Ertel, 1977) was measured in the survey by polling the individuals as to their opinions of the importance of numerous specific related tasks, including the preparation and presentation of educational materials and contact with the media. Results clearly revealed that emphasis in a training course should be placed on tasks of this type, including use of layman's language, effective graphics, and good media coverage.…”
Section: Public Education and Information Transfermentioning
confidence: 99%